Retraction: “Impact of inflation on the macroeconomic indicators in transition economies” published in 2012 (volume 40, issue 2, p. 19-34) - Board, Editorial (Industrija, 2014)
At the initiative of the editors of journal Industrija and without an agreement of the authors, the article by Ranković M., Vasković V. and Simović V. is being retracted.